Human papillomavirus DNA in men who have sex with men: type-specific prevalence, risk factors and implications for vaccination strategies - King, E M (Br J Cancer, 2015)
BACKGROUND: Human papillomavirus (HPV) vaccination of girls will have relatively little effect on HPV-related disease in men who have sex with men (MSM). We determined HPV prevalence and risk factors in MSM to inform the potential effectiveness of vaccinating MSM. METHODS: Cross-sectional study of 522 MSM aged 18–40 attending a London sexual health clinic who completed a computer-assisted self-interview. Urine and two swabs (anal and penile/scrotal/perianal) were collected and tested using an in-house Luminex-based HPV genotyping system. RESULTS: Prevalence of DNA of the vaccine-preventable HPV types in ano-genital specimens of men was 87/511 (17.0%), 166/511 (32.5%) and 232/511 (45.4%) for the bivalent (HPV16/18), quadrivalent (HPV6/11/16/18) and nonavalent (HPV6/11/16/18/31/33/45/52/58) vaccine types, respectively. A total of 25.1% had one of the quadrivalent types, and 7.4% had 2+ types. Median age at first anal sex was 19 (IQR 17–23) and at first clinic attendance was 24 (IQR 20–27). The increase in the odds of any HPV infection per year of age was 4.7% (95% CI 1.2–8.4). CONCLUSIONS: On the basis of the current infection status, most MSM, even among a high-risk population attending a sexual health clinic, are not currently infected with the vaccine-type HPV. A targeted vaccination strategy for MSM in the UK could have substantial benefits.